The evidence of a new magnetic anomaly in Zn-doped LSCO cuprates - Nadareishvili, M.M.; Kvavadze, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The investigations of low-temperature heat capacity in pure (y = 0) and Zn-doped La1.84Sr0.16Cu1–yZnyO4 samples (y = 0.033 and 0.06) have been performed in the interval of 1.8–60 K by a method of high-precision pulsed differential calorimetry, providing the measurements under the equilibrium conditions, in contrast to commonly used differential scanning calorimeters. For these systems a new heat capacity anomaly was observed in the nonsuperconducting state, which is related with Zn impurities and has the form of one wide peak. The anomaly does not show a phonon character as it strongly shifts towards the higher temperatures with the increase of Zn content, which is characteristic for the magnetic anomaly. Anomaly increases almost linearly with the impurity concentration.